1997
DOI: 10.1063/1.364062
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on the resonant tunneling and electric field domain formation in multiple quantum well superlattices

Abstract: Analyzing the photocurrent spectra and the I -V characteristics of weakly coupled GaAs/AlGaAs multiquantum well structures, different transport regimes are distinguished. At low temperatures ͑below ϳ50 K͒, due to the electron coherence over a few periods of the superlattice, electron transport is dominated by sequential resonant tunneling. At higher temperatures, evidences for the increased contribution of nonresonant transport processes, and the subsequent modification in the electric field distribution in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The previous description becomes explicit in the limit δ 1. In such a case, G + = O(1/δ) and G − = −1 with c − = J from equations (150) and (151). The pulse is approximately a straight isosceles triangle with height (F max − F 1 ) ∼ F max because F max 1.…”
Section: (This Figure Is In Colour Only In the Electronic Version)mentioning
confidence: 98%
See 3 more Smart Citations
“…The previous description becomes explicit in the limit δ 1. In such a case, G + = O(1/δ) and G − = −1 with c − = J from equations (150) and (151). The pulse is approximately a straight isosceles triangle with height (F max − F 1 ) ∼ F max because F max 1.…”
Section: (This Figure Is In Colour Only In the Electronic Version)mentioning
confidence: 98%
“…As a result, static EFD formation is much more difficult to observe at room temperature than at liquid He or liquid N 2 temperatures. Kastrup [164] showed that the characteristic branches of static EFD formation disappear in a moderately doped GaAs/AlAs SL for temperatures above about 100 K. Xu et al [151] demonstrated that for a strongly doped GaAs/(Al,Ga)As multiple-quantum-well structure the formation of static EFDs is quenched above about 50 K. Wang et al [165] and Li et al [166] performed a detailed study of the temperature dependence of the I -V characteristics for a moderately doped GaAs/AlAs SL. In the investigation by Wang et al [165], there is a strong change in the shape of the I -V curves between 140 and 145 K. The fine structure of the I -V characteristics completely disappears above 156 K. At the same time, current self-oscillations as discussed in section 5 are already observed at 145 K so that a transition from static to dynamic EFD formation takes place between 140 and 156 K. In the investigation by Wang et al [167] and Li et al [166], who apparently used an identical structure, the fine structure in the I -V characteristics disappears above 170 K, and current self-oscillations appear for temperatures of 180 K and higher.…”
Section: 42mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its practical and theoretical interest, the effect of temperature on electric-field domains [20][21][22] and current selfoscillations is still poorly understood. Early numerical calculations were performed with a fixed drift velocity corresponding to a fixed temperature.…”
Section: Introductionmentioning
confidence: 99%